Image deteriorating factors in cone beam computed tomography, their classification, and measures to reduce them: A pictorial essay - Ajay Ramesh Bhoosreddy; Priyanka Umesh Sakhavalkar (Wolters Kluwer Medknow Publications, 2014)
Cone beam computed tomography (CBCT) is now an established technology in dentistry, used for three-dimensional imaging of the teeth and jaws. But the current CBCT technology has various limitations causing deterioration of images. Every dentist must be familiar with these limitations while interpreting CBCT images. This article aims to present a pictorial essay describing the various CBCT faults and artifacts, which can help to better understand the factors causing image deterioration in CBCT. To further simplify, we are also presenting a classification of these artifacts and listing the measures to reduce them.